The fossil record of freshwater Gastropoda – a global review - Neubauer, Thomas A.; Justus Liebig University Giessen (My University, 2024)
Gastropoda are an exceptionally successful group with a rich and diverse fossil record. They have conquered land and freshwater habitats multiple times independently and have dispersed across the entire globe. Since they are important constituents of fossil assemblages, they are often used for palaeoecological reconstruction, biostratigraphic correlations, and as model groups to study morphological and taxonomic evolution. While marine faunas and their evolution have been a common subject of study, the freshwater component of the fossil record has attracted much less attention, and a global overview is lacking. Here, I review the fossil record of freshwater gastropods on a global scale, ranging from their origins in the late Palaeozoic to the Pleistocene. As compiled here, the global fossil record of freshwater Gastropoda includes 5182 species in 490 genera, 44 families, and 12 superfamilies over a total of ~340 million years. Following a slow and poorly known start in the late Palaeozoic, diversity slowly increased during the Mesozoic. Diversity culminated in an all-time high in the Neogene, relating to diversification in numerous long-lived (ancient) lakes in Europe. I summarise well-documented and hypothesised freshwater colonisation events and compare the patterns found in freshwater gastropods to those in land snails. Furthermore, I discuss potential preservation and sampling biases, as well as the main drivers underlying species diversification in fresh water on a larger scale. In that context, I particularly highlight the importance of long-lived lakes as islands and archives of evolution and expand a well-known concept in ecology and evolution to a broader spectrum: scale-independent ecological opportunity.
Keywords: biodiversity; colonisation; ecological opportunity; long-lived lakes; non-marine Mollusca; palaeogeography; preservation; ddc:570